Simulation of the Abbaji Ammotere Case for Silariang Using Mathematical Modeling in Bugis Society - Rudi; Annas Suwardi; Side Syafruddin; Irwan; Mulbar Usman (ITM Web of Conferences, 2024)
Silariang is a form of deviant behavior that is consciously carried out by men and women by taking shortcuts in marriage without getting the blessing of the family. The causes of silariang are not getting parental approval, cash problems, promiscuity, pregnancy out of wedlock. Abbaji ammotere is an alternative solution to improve relationships with family. This research aims to build a SEIR models. This model is divided into four classes, namely the class of people who have the potential to carry out silariang, the class of people who are affected by carrying out silariang, the people who carry out silariang, and the people who return to their parents (Ammotere Abbaji). The data used is primary data obtained by distributing questionnaires to 204 samples which were carried out offline for silariang perpetrators and online for vulnerable and affected communities. The real data results of the SEIR type model produce a basic reproduction number (R0) of 0,20381767, which means that the range class will experience a significant increase in the sense that at any time they will be affected and practice silariang, while for classes that have practiced silariang this will decrease over a certain period of time.